(untitled) (Kronika Bydgoska, 2013)
In the times of the Polish People’s Republic, the governing Polish United Workers’ Party (PZPR) had at its disposal a network of large circulation dailies, weeklies and monthlies. After the change of the political and economic systems, return to this situation - convenient for the party - was impossible. However, attempts were made at taking over profitable titles by new parties. Owing to the multitude of parties, there was a division into small party periodicals. They are not - as it used to be in the period of the Polish People’s Republic - distributed by retail networks, however, dominant is distribution through party cells or during events co-organised by a given party. None of the titles has gained social support from recipients, who are not party members or sympathizers. Some party publications pretending to be more popular titles can be an abuse.